Influence of the gel thickness on in vivo hyaline cartilage regeneration induced by double-network gel implanted at the bottom of a large osteochondral defect: Short-term results - Matsuda, Hidetoshi (BioMed Central, 2013)
BACKGROUND: A double-network (DN) gel, which is composed of poly(2-acrylamido-2-methylpropanesulfonic acid) and poly(N,N’-dimethyl acrylamide), can induce hyaline cartilage regeneration in vivo in a large osteochondral defect. The purpose of this study was to clarify the influence of the thickness of the implanted DN gel on the induction ability of hyaline cartilage regeneration. METHODS: Thirty-eight mature rabbits were used in this study. We created an osteochondral defect having a diameter of 4.3-mm in the patellofemoral joint. The knees were randomly divided into 4 groups (Group I: 0.5-mm thick gel, Group II: 1.0-mm thick gel, Group III: 5.0-mm thick gel, and Group IV: untreated control). Animals in each group were further divided into 3 sub-groups depending on the gel implant position (2.0-, 3.0-, or 4.0-mm depth from the articular surface) in the defect. The regenerated tissues were evaluated with the Wayne’s gross and histological grading scales and real time PCR analysis of the cartilage marker genes at 4 weeks. RESULTS: According to the total Wayne’s score, when the depth of the final vacant space was set at 2.0 mm, the scores in Groups I, II, and III were significantly greater than that Group IV (p < 0.05), although there were no significant differences between Groups I and IV at a 3.0-mm deep vacant space. The expression levels of type-2 collagen in Groups II and III were significantly higher (p < 0.05) than that in Group IV. CONCLUSIONS: The 1.0-mm thick DN gel sheet had the same ability to induce hyaline cartilage regeneration as the 5.0-mm thick DN gel plug. However, the induction ability of the 0.5-mm thick sheet was significantly lower when compared with the 1.0-mm thick gel sheet. The 1.0-mm DN gel sheet is a promising device to establish a cell-free cartilage regeneration strategy that minimizes bone loss from the gel implantation.